Morphometric analysis of tooth morphology among different malocclusion groups in a hispanic population - Hesham Alsaigh; Murad Alrashdi (BMC, 2023)
Abstract Background There have been reports of unique dental morphological features amongst Latin American and Hispanic populations, and this might invalidate the use of current orthodontic diagnostic tools within this population. There are no tooth size/tooth ratio normative standards for the Hispanic population, despite overwhelming evidence about differences in tooth size between racial groups. Objective This study aimed to determine whether there are significant differences in 3-D tooth shape between patients with Angle Class I, Class II, and Class III dental malocclusion in the Hispanic population. Methodology Orthodontic study models representing Hispanic orthodontic patients with Angle Class I, II, and III dental malocclusions scanned using an intra-oral scanner. The scanned models were digitized and transferred to a geometric morphometric system. Tooth size shape were determined, quantified, and visualized using contemporary geometric morphometric computational tools using MorphoJ software. General Procrustes Analysis (GPA) and canonical variates analysis (CVA) used to delineate the features of shape that are unique to each group. Result The study revealed differences in tooth shape between the different dental malocclusion groups on all twenty-eight teeth that were studied; the pattern of shape differences varied between the teeth and the dental malocclusions. The MANOVA test criteria, F approximations, and P-values show that shape in all the groups was significantly different < 0.05. Conclusion This study revealed differences in tooth shape between the different dental malocclusions on all teeth, and the pattern of shape differences varied between the different dental malocclusions group.